Rhodacarella, a new genus of Rhodacaridae mites from North America (Acari: Mesostigmata: Rhodacaridae) - Moraza, Maria Lourdes (Zootaxa, 2004)
A new genus of mesostigmatic mites, Rhodacarella, is described on the basis of material from bat guano found in a cave in Arizona (U.S.A). Rhodacarella cavernicola sp. nov., is described as the type species of the genus. A key to genera of the subfamily Rhodacarinae is given.